Pengaruh Pajak Daerah, Retribusi Daerah, Hasil Pengelolaan Kekayaan Daerah Yang Dipisahkan Terhadap Pendapatan Asli Daerah Kabupaten/ Kota Di Provinsi Sumatera Utara - Putri Septiana Br. Sigalingging; Muhammad Irsan Nasution, Junawan (STIE AMKOP, 2025)
This study was conducted to analyze the effect of Regional Taxes, Regional Levies and Results of Separated Regional Asset Management on Local Own – Source Revenue. The location of this study is the Regency/City in North Sumatra. This type of research is Associative research with a quantitative approach. The sample of this study was 33 Regencies/Cities in North Sumatra with a period of 5 years, namely 2019 to 2023, resulting in 165 Budget Realization Report reports. The method used is multiple linear regression analysis using SPSS Version 23 software. The results of this study indicate that partially Regional Taxes have a positive effect on Local Own – Source Revenue, Regional Levies have a partial positive effect on regional original income, the results of separated regional wealth management partially have a positive effect on regional original income. While simultaneously all variables of Regional Taxes, Regional Levies and Results of Separated Regional Asset Management, have a simultaneous effect on Local Own – Source Revenue. The contribution of the influence of variables is 85.9%. Keywords: Local Own – Source Revenue, Regional Taxes, Regional Levies, Results of Separated Regional Asset Management.